1995
DOI: 10.1161/01.str.26.5.857
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate-Induced Cerebral Vasodilation Is Mediated by Nitric Oxide Through N -Methyl- d -Aspartate Receptors

Abstract: Glutamate-induced cerebral arteriolar dilation is mediated by NO through NMDA receptors, and NO does not play a major role in the cerebral arteriolar dilation to hypercapnia (PCO2 = 40 to 68 mm Hg) in newborn pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
88
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 41 publications
4
88
1
1
Order By: Relevance
“…Glutamate is a dilator in the cerebral circulation in vivo (8,11,39). Release of glutamate from presynaptic neurons increases blood flow to match the increased metabolic demands of stimulated neurons (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glutamate is a dilator in the cerebral circulation in vivo (8,11,39). Release of glutamate from presynaptic neurons increases blood flow to match the increased metabolic demands of stimulated neurons (37).…”
Section: Discussionmentioning
confidence: 99%
“…Release of glutamate from presynaptic neurons increases blood flow to match the increased metabolic demands of stimulated neurons (37). Neuronal activation in response to excitatory neurotransmitters may affect brain vessels via neurally derived vasorelaxant factors, including NO (11,39,51) and CO (2). Glutamate and selective NMDA-and ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)/kainate receptor agonists increase CO production by piglet cerebral microvessels (29,43) and astrocytes (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the BBB was found to be intact even after 24-h L-glut infusion in rats (20). Third, L-glut and NMDA dilate cerebral arteries in vivo (3,30) but not in vitro (37,44), suggesting that CMVECs do not respond directly to L-glut.…”
mentioning
confidence: 93%
“…IN NEWBORN PIGS, CEREBRAL arterioles dilate to glutamate and its receptor subtype-specific analog N-methyl-Daspartate (NMDA) via a multistep process, involving the activation of NMDA receptors, neuronal production, and release of nitric oxide (NO), and subsequent relaxation of smooth muscle (10,16,25). Because glutamate is the predominant excitatory neurotransmitter in the central nervous system, it has been suggested that this sequence of events may represent one important mechanism for coupling neuronal activity with local blood flow (3,11,16).…”
mentioning
confidence: 99%